Genomic Microsatellites as Evolutionary Chronometers: A Test in Wild Cats - Driscoll, Carlos A.; Menotti-Raymond, Marilyn; Nelson, George; Goldstein, David; O'Brien, Stephen J. (Genome Research, 2002)
Nuclear microsatellite loci (2- to 5-bp tandem repeats) would seem to be ideal markers for population genetic monitoring because of their abundant polymorphism, wide dispersal in vertebrate genomes, near selective neutrality, and ease of assessment; however, questions about their mode of generation, mutation rates and ascertainment bias have limited interpretation considerably. We have assessed the patterns of genomic diversity for ninety feline microsatellite loci among previously characterized populations of cheetahs, lions and pumas in recapitulating demographic history. The results imply that the microsatellite diversity measures (heterozygosity, allele reconstitution and microsatellite allele variance) offer proportionate indicators, albeit with large variance, of historic population bottlenecks and founder effects. The observed rate of reconstruction of new alleles plus the growth in the breadth of microsatellite allele size (variance) was used here to develop genomic estimates of time intervals following historic founder events in cheetahs (12,000 yr ago), in North American pumas (10,000–17,000 yr ago), and in Asiatic lions of the Gir Forest (1000–4000 yr ago).[Supplemental material available online at http://rex.nci.nih.gov/lgd/front_page.htm and athttp://www.genome.org.]
10.1101/gr.185702